Growing-up Slovenia in the nineties - Ule, Mirjana (Družboslovne razprave, 2000)
It is difficult to determine the nature of young people in the 1990s in Slovenia, since this population seems to be socially, culturally and stylistically unformed. The 1960s and the 1970s were years of rapid ascent and qualitative growth for youth movements in Slovenia, along side a higher level of youth emancipation and self-confidence. The 1980s were years of expansion and the breaking up of youth subcultures into the various alternative scenes. The 1990s, in contrast, have been marked by the regression of youth movements, the increased social anomie of youth, and the destruction of alternative youth cultures. The redirection of dealing with society to dealing with oneself is characteristic of the young in Slovenia in the 1990s. Young people deal mostly with themselves now and try to achieve as painless and risk free a path to the future as possible. The problems which they encounter, they do not displace onto society, but deal with them alone.
Keywords: Slovenia; Slovenija; družbene spremembe; tranzicija; mladina; družbeni položaj; družbena diferenciacija; identiteta; subculture; subkultura